Pengembangan Media Pembelajaran Cerita Bergambar Flip Book (CERGAFIBO) pada Mata Pelajaran Akidah Akhlak Kelas VIII MTsN 3 Jombang - Ahmad Maulana Krisna Putra; Khoirun Nisa'; Dian Kusuma Wardani (ANWARUL, 2026)
The use of engaging and visually oriented learning media is necessary to support students’ understanding of moral concepts in the Akidah Akhlak subject, particularly the topic of namimah (tale-bearing). This study aimed to develop the Illustrated Story Flip Book (CERGAFIBO) for eighth-grade students at MTsN 3 Jombang and to evaluate its feasibility, student responses, and effectiveness in improving students’ understanding. The study employed a Research and Development (R&D) method based on the Borg and Gall model, which was adapted to the research needs. The research participants included a subject-matter expert, a media expert, a practitioner or teacher, and eighth-grade students. Data were collected through observation, interviews, validation questionnaires, comprehension tests, and documentation and were then analyzed using quantitative and qualitative descriptive techniques. The results showed that CERGAFIBO obtained average validation scores of 3.8 from the subject-matter expert, 3.2 from the media expert, and 3.75 from the practitioner and was therefore declared feasible for use. Student responses reached 90% in the limited trial and 91.7% in the wider trial, indicating highly positive acceptance of the media. The students’ average comprehension score increased from 60 on the pretest to 85 on the posttest, while learning mastery increased from 50% to 93.3%. This study concludes that CERGAFIBO is feasible for use and can support improvements in students’ understanding of namimah. This medium provides practical implications for developing more interactive, engaging, and visually oriented Akidah Akhlak instruction.